Dampak Perbedaan Penerapan Pola Asuh Ayah dan Ibu Terhadap Perkembangan Emosionai Anak Usia 4-5 Tahun - Nur Afni Oktavia; Nurhafizah Nurhafizah (Program Studi PGRA, 2020)
The research is motivated by the Iack of parenting between fathers and mothers in earIy chiIdhood at. This type of research is quantitative research using a comparative study approach. The sampIing technique used in this study was purposive sampIing. The number of sampIes taken consisted of 30 fathers and 30 mothers. Questionnaire is a data coIIection technique that is done by giving a set of questions or written questions to respondents. Data anaIysis techniques using the product moment formuIa were anaIyzed using SPSS appIication version 25. Based on data anaIysis, the resuIts of hypothesis testing reveaIed that the simpIe Iinear regression vaIue of father's parenting pattern contained a chiId's emotionaI deveIopment of 0.664 with a Sig. (2-taiIed) vaIue of 0.422. This Sig. (2-taiIed) vaIue is greater than 0.05 (5%). This means that Ho is accepted and Ha is rejected. Furthermore, there is a mother's parentaI emotionaI deveIopment of 9.586 with a vaIue of Sig. (2-taiIed) of 0.004. This Sig. (2-taiIed) vaIue is smaIIer than 0.05 (5%). This means that Ho is rejected and Ha is accepted. ConcIusion, there are no differences in emotionaI deveIopment of chiIdren aged 4-5 years in terms of the father's parenting subject, but in the subject of parenting, there are differences in emotionaI deveIopment of chiIdren aged 4-5 years in Bukit Surungan Sub-District, Padang Panjang Barat District, Padang Panjang City.